Functional Outcomes After Feminizing Rhinoplasty - Amin, Luv; Wu, Arthur W.; Chen, Henry H. (Facial Plastic Surgery, 2025)
Feminizing rhinoplasty, as part of facial feminization surgery (FFS), aims to align nasal appearance with gender identity. While nasal obstruction is a known complication of rhinoplasty, its impact on feminizing rhinoplasty is unclear.This study investigates if feminizing rhinoplasty causes nasal obstruction secondary to structural modifications.Prospective cohort study.IRB-approved study included males and females undergoing cosmetic rhinoplasty and transgender females undergoing feminizing rhinoplasty at Cedars–Sinai Medical Center. Nasal obstruction was assessed using the nasal obstruction and symptom evaluation (NOSE) survey preoperatively and 3-, 6-, and 12-months postoperatively, analyzed with a t-test.NOSE scores significantly decreased in all groups, with transgender females showing a 78, 84, and 77% reduction at 3-, 6-, and 12-months. No significant difference was found between cosmetic rhinoplasty and FFS groups postoperatively.Decreases in average NOSE scores across groups suggest that feminizing rhinoplasty does not worsen nasal obstruction and may improve functional outcomes.
Keywords: feminizing rhinoplasty; gender-confirming rhinoplasty; facial feminization surgery